DIAGENETIC ORIGIN FOR QUARTZ-PEBBLE CONGLOMERATES - Cox R.; Gutmann E.D.; Hines P.G (My University, 2002)
The occurrence of quartz-pebble conglomerates (QPC) in the rock record increases backward through time from the Tertiary through the Precambrian. The positive correlation between QPC abundance and age is valid both for numbers of reported QPC and for QPC as a percentage of all conglomerate, and at both the era and the period level. QPC are usually interpreted as being due to intense chemical weathering, protracted transport, or sediment recycling, but none of these can account for the age distribution of QPC, which is the opposite of the global mass-age distribution for sedimentary rocks. Precambrian and Tertiary conglomerates with similar sources and sedimentology have vastly different clast populations, nonquartzose clasts being much more abundant in the younger rocks. Comparison of the petrology of QPC and polymict conglomerates shows that QPC have consistently higher proportions of diagenetic secondary matrix and pressure-solved grain contacts. We conclude that diagenetic factors play an important role in QPC formation by preferentially destroying less durable clasts.
Keywords: clasts; diagenesis; pressure solution; quartz-pebble conglomerates; Precambrian; Докембрий